Assessment of the effectiveness and prospects for the development of the activities of the Ukrainian Chamber of Commerce in conditions of environmental uncertainty - O. M. Vinichenko; N. Yu. Naumenko; L. D. Harmider (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
Today, in an uncertain environment, enterprises, organizations, and citizens need to constantly improve their methods of activity by implementing and applying innovative measures. One of the effective organizations that is in constant development is the Chamber of Commerce and Industry of Ukraine. The organization functions and develops at the expense of a certain number of sources of financial and non-financial revenues (income), which are provided by its effective activities. In order to determine the impact of each type of income of the Chamber of Commerce and Industry of Ukraine, from various types of its activities, on the total amount of income, a correlation-regression model. The most effective source of revenue (income) is the services provided by the organization itself and the institutions created under its auspices. In order to determine the impact of income and expenses on the efficiency of the operations of the Chamber of Commerce and Industry of Ukraine. A multiple linear regression model of the dependence of the financial result of the chamber on its income and expenses was developed. Today, when a significant number of the working population is forced to reside outside Ukraine, the important issue of determining tax residency has arisen. Currently, many Ukrainian citizens living and working abroad are facing an urgent issue: determining their tax residency status under today’s conditions. This problem is the determination of tax residency. The assessment of the activities and identification of existing and potential opportunities of the Ukrainian Chamber of Commerce and Industry allowed us to propose an expansion of the organization's services by involving the chamber in the service of determining the tax residence of citizens who currently live and work abroad, but have income in Ukraine as well. This, on the one hand, will ensure an increase in the chamber’s income without a significant increase in costs and, on the other hand, a high-quality service and connection with the homeland for a certain category of Ukrainian citizens.